Strengthening the Role of PKK Members in Maintaining Family Health in Jomblangan Village - Ai Sumirah Setiawati; Ratri Ciptaningtyas; Sri Panca Setyawati; Kurnia Indriyanti Purnama Sari; Lina Maulidiana; Marina Pakaya; Lathifah Hanum; Bambang Sugiharto; Widhiya Ninsiana; Lilik Yulianingsih (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The role of PKK members is crucial in promoting health at the family and community levels in Indonesia. This community service project aimed to strengthen the role of 17 PKK members in Jomblangan Village through structured health education and empowerment training. Utilizing a participatory action approach, the program focused on five thematic areas: balanced nutrition, stunting prevention, hygiene and sanitation, maternal and child health, and home-based first aid. Data were collected through pre- and post-tests, observation, and focus group discussions. The average knowledge score increased by 29%, and participants demonstrated behavioral changes such as improved dietary practices, regular growth monitoring, and proper hygiene habits. Qualitative data also revealed enhanced motivation and willingness to share knowledge within the community. The findings confirm that PKK members, when equipped with appropriate knowledge and skills, can become effective grassroots health promoters. The program proved effective, acceptable, and replicable, providing a scalable model for similar communities. Continuous mentoring and digital engagement are recommended for long-term sustainability.